Pelatihan Pengelolaan Keuangan dan Permodalan Bagi UMKM di Desa Kertomulyo - Yuni Astuti, Fitria; Hani, Umi; Pujiastuti, Arum (STIKes Ibnu Sina Ajibarang, 2025)
This community service program aims to improve the financial literacy and financial management skills of micro and small business (MSME) actors in Kertomulyo Village, Brangsong District, Kendal Regency. The main issues faced by local residents include limited access to formal financial institutions and a lack of understanding of business financial planning. The activity was held on November 19, 2024, using both classical and individual approaches, including lectures, demonstrations, and hands-on practice. Training materials covered budgeting, identifying funding sources, setting profit targets, and evaluating financial plans. A total of 60 MSME participants actively took part in the training. The results show increased participant understanding of basic financial management concepts, although further assistance is still needed by some. This activity demonstrates that practical-based training is effective in improving MSME financial capabilities and can serve as a replicable model for other regions facing similar challenges.